2012
DOI: 10.1186/1471-2229-12-80
|View full text |Cite
|
Sign up to set email alerts
|

In silico polymorphism analysis for the development of simple sequence repeat and transposon markers and construction of linkage map in cultivated peanut

Abstract: BackgroundPeanut (Arachis hypogaea) is an autogamous allotetraploid legume (2n = 4x = 40) that is widely cultivated as a food and oil crop. More than 6,000 DNA markers have been developed in Arachis spp., but high-density linkage maps useful for genetics, genomics, and breeding have not been constructed due to extremely low genetic diversity. Polymorphic marker loci are useful for the construction of such high-density linkage maps. The present study used in silico analysis to develop simple sequence repeat-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 61 publications
8
122
1
4
Order By: Relevance
“…Progeny are vigorous, phenotypically normal and fertile and showed lower segregation distortion 16,17 than has been observed for some populations derived from A. hypogaea intraspecific crosses [18][19][20][21] . Therefore, as a first step to characterizing the genome of cultivated peanut, we sequenced and analyzed the genomes of the two diploid ancestors of cultivated peanut.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Progeny are vigorous, phenotypically normal and fertile and showed lower segregation distortion 16,17 than has been observed for some populations derived from A. hypogaea intraspecific crosses [18][19][20][21] . Therefore, as a first step to characterizing the genome of cultivated peanut, we sequenced and analyzed the genomes of the two diploid ancestors of cultivated peanut.…”
mentioning
confidence: 97%
“…Of the marker sequences from three maps 21,41 , 83%, 83% and 94% were assigned by sequence similarity searches to the expected diploid chromosomal pseudomolecules (Supplementary Data Set 6). When visualized as plots along the chromosomal pseudomolecules, the diploid A-genome chromosomes were distinctly less similar to A. hypogaea sequences than the B-genome chromosomes (Fig.…”
Section: Sequence Comparisons To Tetraploid Cultivated Peanutmentioning
confidence: 99%
“…Resistance to biotic stresses Angular leaf spot QTL 22-64 Oblessuc et al, 2012;Teixeira et al, 2005 (Khedikar et al, 2010;Liang et al, 2009a;Qin et al, 2012;Sujay et al, 2012;Wang et al, 2013 (Gautami et al, 2012b;Ravi et al, 2011;Varshney et al, 2009b) Gautami et al, 2012a;Liang et al, 2009;Ravi et al, 2011;Selvaraj et al, 2009;Shirasawa et al, 2012;Varshney et al, 2009b) (Continued on next page) (Liang et al, 2009;Pandey et al, 2012c;Sarvamangala et al, 2011;Selvaraj et al, 2009;Shirasawa et al, 2012) Pea Plant height QTL 19-65 (Tullu et al, 2008;Tar'an et al, 2003b;Dirlewanger et al, 1994) (Atibalentja et al, 2005;Guo et al, 2006;Guo et al, 2008;Han et al, 2008;Huynh et al, 2010;Kazi et al, 2008;Ruben et al, 2006;Shi et al, 2008;Silva and Danielle, 2008;Vuong et al, 2008;Wang et al, 2010;Winter et al, 2007) (Continued on next page) Funatsuki et al, 2005;Githiri et al, 2006;Githiri et al, 2007;…”
Section: Common Beanmentioning
confidence: 99%
“…In addition to the SSRs mentioned above, Wang et al (2012) have also used 1152 SSRs mined from 36,314 BAC-end sequences (BES) and constructed a genetic map with a total of 318 markers covering 1674.4 cM in a single mapping population. For the creation of the highest density map of a single population of cultivated peanut to date, Shirasawa et al (2012b) reported the use of in silico analysis of DNA sequence data from the parental lines, which increased the efficiency of polymorphic marker development by more than three-fold. In total, 926 (34.2%) of 2702 markers showed polymorphisms between parental lines of the mapping population.…”
Section: Recent Advancement In Genetic Linkage Mapsmentioning
confidence: 99%
“…In total, 926 (34.2%) of 2702 markers showed polymorphisms between parental lines of the mapping population. Linkage analysis of the 926 markers along with 253 polymorphic markers selected from 4449 published markers generated 21 linkage groups covering 2166.4 cM with 1114 loci (Shirasawa et al, 2012b).…”
Section: Recent Advancement In Genetic Linkage Mapsmentioning
confidence: 99%